Studi Kesiapan Digital pada UMKM Kecil di Jakarta Barat Menggunakan TOE Framework - Syahrul Naufalrafa; Qori Halimatul Hidayah; Hani Dewi Ariessanti; Sawali Wahyu (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study analyzes the digital readiness of Micro, Small, and Medium Enterprises (MSMEs) in West Jakarta using the Technology-Organization-Environment (TOE) framework, with a qualitative case study at Toko Lily and quantitative validation on a similar MSME population. Adopting a mixed-methods approach with a sequential exploratory design, data was collected through in-depth interviews and observations at Lily's Store, as well as the distribution of questionnaires to 90 MSME managers in West Jakarta. Qualitative results indicate that Toko Lily has high readiness, driven by awareness of the benefits of technology, owner support, financial resources, and basic digital competencies of employees, plus pressure from customers and competitors. Quantitatively, SmartPLS analysis confirmed that the Technology, Organization, and Environment dimensions positively and significantly influence SME digital readiness in West Jakarta (R²=0.596), indicating a strong foundation of readiness. This study underscores the relevance of TOE in the context of traditional SMEs, enriches the literature with mixed-methods evidence, and recommends a phased digitalization roadmap as a practical guide to enhance SMEs' efficiency and market reach.